A Review of the Application of Hemispherical Photography in Urban Outdoor Thermal Comfort Studies - Lei Sima; Yisha Liu; Xiaowei Shang; Qi Yuan; Yunming Zhang (Buildings)
Thermal comfort studies are paramount in enhancing future urban living conditions, and hemispherical photography has emerged as a widely employed field measurement technique in outdoor thermal comfort research. This comprehensive review systematically analyzed 142 outdoor thermal comfort studies conducted over the past decade using hemispherical photography methods, revealing that its primary application lies in objectively describing environmental information and constructing associated indices. In contrast, the number of studies focusing on subjectively assessing environmental factors remains relatively low; however, it is rapidly increasing due to its demonstrated effectiveness and convenience compared to other methodologies within this domain. Overall, despite certain limitations, such as higher labor costs and limited temporal/spatial coverage when describing environmental information, hemispherical photography still retains its advantage of providing accurate data acquisition for outdoor thermal comfort research. In recent years, advancements in mobile measurement tools and techniques have enhanced the richness and versatility of acquired information while leveraging the image specificity inherent to hemispherical photography, which continues to play a pivotal role in subjective assessments related to human perception of outdoor thermal comfort.